A comparative study of NaOH and KOH electrolytes in micro-ECM. Issue 4 (2nd October 2022) - Zishanur Rahman, Md.; Das, Alok Kumar; Chattopadhyaya, Somnath
ABSTRACT: Tungsten microtool electrode is one of the preferred tool electrodes in micro electrochemical machining (µECM) of hard to machine materials. During the pilot experiments with different types of electrolytes materials (such as NaOH, HNO3, NaBr, KOH, H2 SO4, NaCl, NaNO3 and HCl), it has been found that KOH(Aq.) and NaOH(Aq.) electrolytes are suitable for the fabrication of tungsten microtools through µECM process. Therefore in this research, a comparative study between NaOH(Aq.) and KOH(Aq.) electrolytes have been carried out in the fabrication of tungsten microtools through µECM. DC voltage (V), electrolyte concentration (Mol/L) and machining time (Minutes) are chosen as machining parameters in order to investigate their role on response outputs i.e. tool radius reduction (Δ) and material removal rate (MRR). Roles of machining parameters on the response output are analysed through Taguchi design technique and ANOVA is employed to determine the dominant machining parameters on the response outputs. Experimental results indicate 'Δ' and 'MRR' obtained with NaOH(Aq.) is greater than 'Δ' and 'MRR' obtained with KOH(Aq.) respectively at most of the experimental run. But microscopic view of the fabricated microtools indicate that the surface uniformity throughout the length of the microtools obtained with KOH(Aq.) electrolyte is favourable than NaOH(Aq.).